Medicare Data Reveal Wide Variety Across Regions Of COVID-19 Fatality Risk - Morden, Nancy E.; Skinner, Jonathan; Weeks, Bill; Tomlin, Stephanie; Weinstein, James (Health Affairs, 2020)
Early evidence makes clear that some Americans are at much greater risk than others of severe COVID-19 symptoms, hospitalization, and death; less is known about which regions are especially vulnerable. In this post, we describe a collaboration between Microsoft Healthcare NeXT and Dartmouth Atlas Project researchers aimed at measuring the risk of severe COVID-19 across regions of the U.S.